Morphological ontogeny of Oribatella reticulata (Acari: Oribatida: Oribatellidae). Issue 2 (17th February 2021) - Seniczak, Stanisław; Ivan, Otilia; Marquardt, Tomasz; Seniczak, Anna
ABSTRACT: The morphological ontogeny of Oribatella reticulata Berlese, 1916 is described and illustrated. The nymphs of this species are apopheredermous, i.e. they carry the exuvial scalps of previous instars away from the dorsal integument, using modified setal pair da . The larva has 12 pairs of gastronotal setae, including short h 3, the nymphs have 15 pairs, and most are long and barbed. In all juveniles, a humeral organ is absent, which is unique in Oribatella . The tritonymph of this species has more thickened setae on leg segments ( d on all femora and genu IV, ev' on femora III and IV, l on femora I–III and genua and tibiae I–IV) than the adult ( l" on genua and tibiae I and II, l' on genu and tibia IV).